Effect of masonry wall on Strength and Ductility in common RC frame low storey buildings - Anup Poudel; Rajan Suwal (Advances in Engineering and Technology: An International Journal, 2023)
The Nepal National Building code (NBC) was promulgated in 2003 and is divided into four different parts in order to cover buildings constructed in Nepal. NBC 105 has undergone a major update in 2020 with its repercussions on existing prevalent buildings. So, in this paper effort has been made to understand municipal drawings submitted to municipalities constructed with current prevalent building construction practice with column size of 300mm x 300mm, 300mm x 230mm and 230mm x 230mm. Moreover, effects of masonry infill are considered with a separate model considering an equivalent strut as per IS 1893:2016. Ten sample buildings were selected after a rigorous sampling process of over 5000 municipal drawings to represent typical buildings. Non-linear static pushover analysis was conducted on those ten buildings and twenty models. There has been an increase in the over-strength factor of the buildings while there was reduction in ductility factor of the buildings. Equations are proposed based on non-linear regression analysis to determine the changes in over-strength and ductility factor of the buildings.